Deregulation and relative wages: Stability and change in Australia - Preston, Alison (Curtin University of Technology, 2000)
In Australia the pace of labour market deregulation has rapidly accelerated overthe 1990s. This paper uses the recent developments in the Australian labourmarket to provide further insight into the effects of deregulatory policies on labourmarkets and labour. Does labour market deregulation have an equivalent impacton different labour market groups? Two wage indicators (the gender pay gap andthe wage differential between part-time and full-time workers) are used to answerthese questions. The paper shows that over the first half of the 1990s there wasno change in the gender wage gap in the full-time labour market (equal to 10.5per cent), a 12.6 percentage point convergence in the gender wage gap in thepart-time labour market, and a 3.4 percentage point convergence in the parttime/full-time wage gap. Changes in the part-time labour market may beattributed to a deterioration in the relative earnings of males employed part-time.